Examining Polyethylene Terephthalate (PET) as Artificial Coarse Aggregates in Concrete - Bachtiar, Erniati; Mustaan, Mustaan; Jumawan, Faris; Artayani, Meldawati; Tahang, Tahang; Rahman, Muhammad Junaedy; Setiawan, Arman; Ihsan, Muhammad (Salehan Institute of Higher Education, 2020)
This study aims to examine the effect of recycled Polyethylene Terephthalate (PET) artificial aggregate as a substitute for coarse aggregate on the compressive strength and flexural strength, and the volume weight of the concrete. PET plastic waste is recycled by heating to a boiling point of approximately 300Â°C. There are five variations of concrete mixtures, defined the percentage of PET artificial aggregate to the total coarse aggregate, by 0, 25, 50, 75 and 100%. Tests carried out on fresh concrete mixtures are slump, bleeding, and segregation tests. Compressive and flexural strength tests proceeded based on ASTM 39/C39M-99 and ASTM C293-79 standards at the age of 28 days. The results showed that the use of PET artificial aggregate could improve the workability of the concrete mixture. The effect of PET artificial aggregate as a substitute for coarse aggregate on the compressive and flexural strength of concrete is considered very significant. The higher the percentage of PET plastic artificial aggregate, the lower the compressive and flexural strength, and the volume weight, of the concrete. Substitution of 25, 50, 75 and 100% of PET artificial aggregate gave decreases in compressive strength of 30.06, 32.39, 41.73 and 44.06% of the compressive strength of the standard concrete (18.20 MPa), respectively. The reductions in flexural strength were by respectively 19.03, 54.50, 53.95 and 61.00% of the standard concrete's flexural strength (3.59 MPa). The reductions in volume weight of concrete were by respectively 8.45, 17.71, 25.07 and 34.60% of the weight of the standard concrete volume of 2335.4 kg/m3Â Doi: 10.28991/cej-2020-03091626 Full Text: PDF